Leo Strauss: the early writings, 1921-1932 - Strauss, Leo; Zank, Michael (SUNY series in the Jewish writings of Strauss, 2002)
Front Matter -- Half Title Page -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Acknowledgments -- Abbreviations -- Part I: Introduction -- Part II: Leo Strauss: Early Publications (1921-32) -- The Dissertation (1921) -- Zionist Writings (1923-25) -- Historical-Philological Writings on Spinoza (1924-26) -- Reorientation (1928-32) -- Back Matter -- Index of Sources -- General Index -- Back Cover.